Analysis of Websites Supplying Computer Games in the Assessment of Users - Chmielarz, Witold; Szumski, Oskar (International Journal of Engineering and Technology, 2018)
The aim of this article is to execute a comparative analysis of delivery methods used to purchase computer games. The article is a continuation of research focused on the popularity, use and impact of games on the behavior of a prominent population. For the analysis it was chosen the nine most common computer game stores found in the first hundreds of searches in Google. CAWI analyzes were used for six groups of features: transparency, site navigation, quality of information, product search quality, advertising, and the quality of the order processing from the customer's perspective. A qualitative study was conducted to select a sample of selected students using the point method and the point method with preferences to evaluate the distinctive features of the services. A group of over two hundred and fifty randomly selected people from the university was examined. This approach was based on the structure of the article consisting of the presentation of the research hypothesis, the description of the methodology and the research sample, and the analysis of the results and their discussion together with the resulting conclusions. The results of the work may be used by the owners of computer games and website designers.Â Â